Association between non-alcoholic fatty liver disease and subclinical atherosclerosis in Western and Asian cohorts: an updated meta-analysis - Rehena Sultana; Khung Keong Yeo; Mark Yu Zheng Wong; Jonathan Jiunn Liang Yap; Mark Cheah; George Boon Bee Goh (Open Heart)
Background Non-alcoholic fatty liver disease (NAFLD) is a well-established risk factor for cardiovascular disease, with ethnic and regional differences noted. With the recent surge of research within this field, we re-examine the evidence associating NAFLD with subclinical atherosclerosis, and investigate potential regional differences.Methods This is a systematic review and meta-analysis. PubMed and EMBASE were systematically searched for publications from January 1967 to July 2020 using standardised criteria. Original, observational studies investigating the association between NAFLD and either carotid intima-media thickness (CIMT) and/or coronary artery calcification (CAC) were included. Key outcomes included differences in mean CIMT, the presence of increased CIMT, the presence of CAC and the development/progression of CAC. Pooled ORs and pooled standard differences in means were calculated using random-effects models. Between-study heterogeneity was quantified using the Q statistic and I². Subgroup analyses stratified by region of study (Asian vs Western) were also conducted.Results 64 studies involving a total of 172 385 participants (67 404 with NAFLD) were included. 44 studies assessed the effect of NAFLD on CIMT, with the presence of NAFLD associated with increased CIMT (OR 2.00, 95% CI 1.56 to 2.56). 22 studies assessed the effects of NAFLD on CAC score, with the presence of NAFLD associated with the presence of any coronary calcification (OR 1.21, 95% CI 1.12 to 1.32), and the development/progression of CAC (OR 1.26, 95% CI 1.04 to 1.52). When stratified by region, these associations remained consistent across both Asian and Western populations (p>0.05). The majority (n=39) of studies were classified as ‘high quality’, with the remaining 25 of ‘moderate quality’.Conclusions There is a significant positive association between various measures of subclinical atherosclerosis and NAFLD, seen across both Western and Asian populations. These results re-emphasise the importance of early risk evaluation and prophylactic intervention measures to preclude progression to clinical cardiovascular disease in patients with NAFLD.